Treatment of hypertension in patients with chronic kidney disease - Arnold Kukowka; Tomasz Sroczyński; Mariusz Pluskota; Maria Kuczmarz (Polish Pharmaceutical Society, 2021)
Chronic Kidney Disease (CKD) is a global disease of the modern age. In 2017, 679 million people had suffered from CKD, and around 1.3 million patients had died from it. CKD is intrinsic to hypertension in two aspects. Firstly, hypertension can damage the kidney creating a hypertensive nephropathy which is one of the most common etiology for chronic kidney disease. Secondly, CKD can be a cause of hypertension due to volume overload, salt retention, sympathetic hyperactivity, endothelial dysfunction, and changes in hormonal systems that regulate blood pressure. The majority of the hypertensive medications are nephrotoxic and their application depends on the level of GFR. The research paper focuses on the main groups of the medications for hypertension, their effects on the functioning of kidneys, and their possible application in hypertension and CKD treatment. What is discussed in the article are the medications that affect the renin-angiotensin-aldosterone system such as direct renin inhibitors (DRI), angiotensin receptor blockers (ARB), angiotensin-converting-enzyme inhibitors (ACEI), as well as mineralocorticoid receptor blockers (MRB). Additionally, the paper analyses calcium channel blockers (CCB), diuretics, sympatholitics, beta-blockers, alpha-adrenergic receptor antagonists, and vasodilators. The most commonly used groups of pharmaceuticals are those that affect renin-angiotensin-aldosterone system, calcium channel blockers and diuretics; some of which are recent and some invented years back yet still effective in decreasing blood pressure. These medicaments can be combined; however, it depends on the clinical condition of a patient. A variety of therapeutic options makes it possible to apply appropriate treatment for a patient. What the research paper emphasizes is the multiplicity of drug groups that can be used in treatment of these coexisting diseases. Doctors and scientists must continuously expand their knowledge on antihypertensive treatment, and how to appropriately adjust treatment to a patient's needs.